Ocorrência de endoparasitas gastrointestinais em cães da associação protetora animal e ambiental da cidade de Patos de Minas, MG, Brasil: OCCURRENCE OF GASTROINTESTINAL ENDOPARASITES IN DOGS FROM THE ASSOCIAÇÃO PROTETORA ANIMAL E AMBIENTAL DE PATOS DE MINAS, OF THE CITY OF PATOS DE MINAS, MG, BRAZIL (Veterinária Notícias, 2021)
This study aimed to investigate the occurrence of gastrointestinal parasites in dogs from the Associação Protetora Animal e Ambiental de Patos de Minas (ASPAA), in the city of Patos de Minas, MG. 100 dogs sheltered from April 2017 to February 2018 were evaluated. A sample of fhesh feces from each animal was collected and submitted to the techniques of Hoffman, Pons and Janer (1934) and Willis and Mollay (1921). The main helminth eggs found were Ancylostoma sp. and Toxocara canis, and the coccid class protozoan Isospora canis. Infection caused by Toxocara canis and Ancylostoma sp. was prevalent, emphasizing a threat to public health, considering the close proximity between man and dog and the zoonotic potential of the main genera found in this study.